2017
DOI: 10.1007/s11999-016-5107-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Shallow Acetabulum With a Combination of Autologous Bulk and Impaction Bone Grafting Fixed by Cement

Abstract: BackgroundAcetabular bone deficiency, especially proximal and lateral deficiency, is a difficult technical problem during primary total hip arthroplasty (THA) in developmental dysplasia of the hip (DDH). We report a new reconstruction method using a medial-reduced cemented socket and additional bulk bone in conjunction with impaction morselized bone grafting (additional bulk bone grafting method).Questions/purposesIn a population of patients with acetabular dysplasia undergoing THA using a medial-reduced cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…In the literature, Abdel et al 9 who performed arthroplasty using a femoral head graft reported a mean acetabular component diameter of 48 ± 5.2 mm (range 42–58 mm), and Maruyama et al, 21 in their 102-case study, observed that the acetabular component diameter was 40–50 mm; more than half of the patients had an acetabular component of 48 mm. In the present study, the mean acetabular cup diameter was 49 mm (range 40–60 mm), which is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, Abdel et al 9 who performed arthroplasty using a femoral head graft reported a mean acetabular component diameter of 48 ± 5.2 mm (range 42–58 mm), and Maruyama et al, 21 in their 102-case study, observed that the acetabular component diameter was 40–50 mm; more than half of the patients had an acetabular component of 48 mm. In the present study, the mean acetabular cup diameter was 49 mm (range 40–60 mm), which is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, results related to the use of bone autografts vary, which has been attributed to differences in patient selection, degree of dysplasia, patient age and bone quality, grafting technique, graft coverage percentage, and choice of the component. [20][21][22] The use of high hip center technique provides an attractive alternative for reconstruction of the deficient acetabulum. Excellent outcomes, as shown by a minimum 10-year follow up, were accomplished with the high hip center placed by different authors.…”
Section: Discussionmentioning
confidence: 99%
“…Five methods have been reported for dysplastic hips: proximal positioning of the socket, customized acetabular augments, combination with trabecular metal, bulk bone grafting on the roof of the acetabulum, and impaction bone grafting [ 25 , 26 ]. We advocated that bulk bone grafting is the best in terms of the bone stock and cup position.…”
Section: Discussionmentioning
confidence: 99%
“…also used cemented cups combined with bulk bone graft to treat dysplasia hips, and after a mean 8 years found no signs of graft collapse or cup loosening. Maruyama et al . used cemented cup combined with bulk bone and impaction bone grafting to treat dysplasia hips.…”
Section: Confirmation Of Acetabular Positionmentioning
confidence: 99%